Corrigendum: Atomic real-space perspective of light-field-driven currents in graphene (2022 New J. Phys. 24 033051) - Yuya Morimoto; Yasushi Shinohara; Kenichi L Ishikawa; Peter Hommelhoff (New Journal of Physics, 2023)
In the published version of the paper, we made an error in choosing the value of the effective nuclear charge Z in equation (7). The correct value is Z = 4.00. Correcting this does not affect the main claims of the work, namely, the atomic-scale maps of the obtained currents and the Rabi oscillations appearing in the real-space charge densities. We also correct typographical errors in equation (10) and that in the definition of the hopping integral $γ $ , and add a normalization constant in equation (7) for better clarity.